2017
DOI: 10.1007/s10943-017-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spirituality in Lifestyle Changing Among Patients with Chronic Cardiovascular Diseases: A Literature Review of Qualitative Studies

Abstract: Chronic cardiovascular diseases (CVD) are diseases with marked morbidity. Patients are often advised to change their lifestyle to prevent complications and impairment of their diseases. Compliance, however, is influenced by multiple factors. Initial studies show that spirituality is an important aspect in health behavior and lifestyle changing, but to health professionals like nurses this is unknown. The aim of this review is to investigate and synthesize evidence about the role of spirituality in lifestyle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
2
15
0
15
Order By: Relevance
“…Women reported that they seek meaning and purpose in their illness, and for some this implied turning to religion and spirituality (Chiaranai, 2014; Crane & McSweeney, 2003; Darr et al, 2008; LaCharity, 1999; Najafi Ghezeljeh & Emami, 2014; Turman, 1995). This finding supports the result of a review of 12 qualitative studies (Janssen-Niemeijer, Visse, Van Leeuwen, Leget, & Cusveller, 2017), which found spirituality to be related to the self-management of CVD. Religion gave strength in the battle for lifestyle changes and was a source of social support.…”
Section: Discussionsupporting
confidence: 88%
“…Women reported that they seek meaning and purpose in their illness, and for some this implied turning to religion and spirituality (Chiaranai, 2014; Crane & McSweeney, 2003; Darr et al, 2008; LaCharity, 1999; Najafi Ghezeljeh & Emami, 2014; Turman, 1995). This finding supports the result of a review of 12 qualitative studies (Janssen-Niemeijer, Visse, Van Leeuwen, Leget, & Cusveller, 2017), which found spirituality to be related to the self-management of CVD. Religion gave strength in the battle for lifestyle changes and was a source of social support.…”
Section: Discussionsupporting
confidence: 88%
“…17 Patients with MI need to have a peaceful and calm living environment to be able to live without symptoms. In this context, spirituality is a practical approach to achieve this goal, 56 because it provides strengths to the patients to strive and overcome the negative aspects of the disease. 57…”
Section: Discussionmentioning
confidence: 99%
“…Spiritualitas memiliki dampak positif pada kesehatan dan kesejahteraan dan mendukung orang dengan penyakit kronis untuk mendorong tanggung jawab pribadi untuk kesehatan dan kesejahteraan. Selanjutnya, spiritualitas juga diidentifikasi sebagai strategi mengatasi dalam mengelola penyakit kronis (Leeuwen, 2017) .…”
Section: Pendahuluanunclassified